Tibet and China’s Orientalists: Knowledge, Power, and the Construction of Minority Identity - Powers, John (Journal of global buddhism, 2018)
This article explores the salience of Edward Said's characterization of European Orientalists to contemporary Chinese academics working on Tibetan Buddhism. While Said's work has been criticized for selective citations and for focusing on work that is long out of date, Orientalist tropes are pervasive in current tibetological work published in China, including articles in purportedly scholarly journals. This work is closely connected with government propaganda, and it is often explicitly directed by members of the government to further agendas of suppression. Equally importantly, the article examines the ways in which Tibetans are presented with a version of their religion that bears little or no resemblance to how they traditionally have understood it; but it is also an image that Tibetans are increasingly being coerced to endorse.